Revisiting social foundations and well-being indicators for sustainability: Insights from a systematic literature review - Jing Li; Anne Warchold; Prajal Pradhan (Ecological Indicators, 2025)
A growing number of sustainability studies establish well-being frameworks for building social foundations within environmental limits. Numerous indicators are used to track and monitor the progress of well-being. Yet, the overlap and differences among frameworks limit a holistic, consolidated, and systemic understanding. Our systematic literature review addresses this gap, identifying 108 papers on well-being in sustainability studies and compiling a dataset of 725 unique socioeconomic indicators across these studies. We compared these indicators with two major frameworks, the ‘Safe and Just Space for Humanity’ and the ‘2030 Agenda’ with its Sustainable Development Goals, as well as other well-being frameworks. We identified an unequal distribution of indicators, with objective indicators predominating over subjective ones, highlighting the need for a more balanced approach to measure well-being. We also identified indicators beyond existing frameworks and developed an integrated social foundation by incorporating indicators across five themes and 21 dimensions. Our framework integrates individuals, social groups, society, and the environment, considering future impacts and various forms of equity. Doing so will enhance the clarity and efficacy of well-being indicators, support policy-making, and achieve social foundations within planetary boundaries.